PENGARUH PEMIKIRAN KEAGAMAAN LASKAR JIHAD AHL AL-SUNNAH WA AL-JAMAAH DI AMBON - Muhammad Arief Budiyanto (IAIN Ambon, 2018)
The development and dinamica of thought amongst groups always keep on in diversity. For instant, the thoughts of mu’tazilah which is liberal is against those of As’ariyah and Maturidiyah which proclaim Ahl Al-Sunnah wa Al-Jamaah. Each thought which is lead by Ja’far Umar Thalib. This thought is more known with Laskar Jihad Ahl Al-Sunnah wa al-Jamaah. This thought has 3 basic teaching; tauhid (pure oneness), hadis (the Prophet’s saying) and the thought of salafiyyin. This teaching has spreaded in Ambon, it’s aimed to give an aid in struggling (jihad) against the Kafiruun (the disbelievers). Before the coming of Islamic Shari’a, either in Tauhid, shari’a or jihad (struggle). Nevertheless, after the Laskar Jihad came, those sinful acts has been eliminated